Pemanfaatan Biodiversitas Pesisir sebagai Mitigasi Bencana: Pembelajaran Project di SMK Negeri 1 Batudaa Pantai Provinsi Gorontalo - Herinda Mardin; Ilyas H. Husain; Masra Latjompoh; Jusna Ahmad; Chairunnisah J. Lamangantjo (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Natural disasters like earthquakes, tidal floods, and strong winds frequently occur in coastal areas, necessitating disaster mitigation. Coastal biodiversity can serve as a tool for disaster mitigation in coastal areas. SMK Negeri 1 Batudaa Pantai, located in the coastal area of Tomini Bay, Gorontalo Province, conducts community service activities regarding the use of coastal biodiversity as disaster mitigation due to the importance of this knowledge for coastal communities. This activity was attended by 41 students from classes X and XI at SMK Negeri 1 Batudaa Pantai. On May 20, 2024, the SMK Negeri 1 Batudaa Pantai school building hosted the activity from 8:00 WITA until its conclusion. Lecture, discussion, and active participation are methods used in activities. Service activities run well and smoothly. Participants were enthusiastic about participating in this activity, which provided benefits. This activity benefits participants by enhancing their understanding of how to utilize coastal biodiversity to prevent unwanted natural disasters. The importance of knowing coastal biodiversity as disaster mitigation can minimize the occurrence of natural disasters in coastal areas.